Conservation of a specialised species is helpful for the whole ecosystem: a case study of Hylaeus pectoralis (Hymenoptera: Colletidae) - Bogusch, Petr; Houfková Marešová, Petra; Falk, Steven; Astapenková, Alena; Heneberg, Petr (Journal of insect conservation, 2024)
Wetlands belong to the most endangered habitats in the world, and animals and plants occurring there are subjects of nature conservation efforts worldwide. Several species of bees and wasps have been comprehensively studied in recent years, but the biology and ecology of wetland-associated species remain largely enigmatic. The results showed that some of these species can be good bioindicators, useful in nature conservation. Hylaeus pectoralis is a small wetland-associated bee that is dependent on the presence of its nesting resource, cigar galls formed by the frit fly Lipara lucens on stems of common reed. We studied the presence of this bee species between 2011 and 2023, both in near-natural and anthropogenic habitats. This bee requires the presence of terrestrial reed with reed galls and occurs nearly exclusively in long-lasting localities of near-natural character with wet meadows rich in flowering plants. Our results showed that H. pectoralis requires mosaic sites with reed beds combined with wet meadows. The proportion of wet meadows in the H. pectoralis localities is more prominent than in localities where H. pectoralis was absent. The bee is polylectic, and we enlarged the number of pollen sources to plants of 22 families—the collected pollen was from plants of many habitats, including plants of wet meadows and aquatic plants. Though recording of H. pectoralis in the locality is simple using the rearing from collected reed galls, this ecologically sensitive species can be used as an essential bioindicator for the quality of wetland habitats and the studies of the continuity of the habitats. Implications for insect conservation The presence of the mosaic of wet meadows with flowering plants, small reed beds, reed margins, and small water reservoirs is necessary not only for Hylaeus pectoralis but also for other biota of wetlands. Mowing of reed margins should be implemented to only a part of the habitat. This mosaic management allows the preservation of old Lipara -induced galls needed for nesting of ecologically sensitive bees and wasps.